DEVELOPING PRONUNCIATION SKILLS IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE: A PHONETIC AND PROSODIC APPROACH (Web of Teachers: Inderscience Research, 2026)
The article examines the features of developing pronunciation skills in teaching Russian as a foreign language. It analyzes the main phonetic and prosodic difficulties encountered by foreign learners and their impact on oral speech quality and comprehension. Special attention is paid to the role of intonation, rhythm, and stress in the formation of phonetic competence. The study substantiates the necessity of systematic phonetic instruction at the elementary and intermediate stages of teaching Russian as a foreign language. Methodological techniques and exercises aimed at developing listening–pronunciation skills and improving the communicative effectiveness of speech are proposed.